Natural disasters, investor attention, and non-fundamental green asset demand - Marina A. Misev; Patrick Balles (University of Basel, Center of Business and Economics (WWZ), 2024)
This study examines how the occurrence of natural disasters in the U.S. influences investor interest in green assets and actual investments, focusing on inflows into green ETFs as a proxy for non-fundamental demand. Event study analyses demonstrate both increases in investor interest in eco-friendly investments (proxied by Google searches) and inflows into green ETFs following disasters, driven by the period following the 2015 Paris Agreement. The additional inflows average about 4.3 million in the week directly following disasters, compared to average inflows of around 1.1 million in the non-disaster reference window. Importantly, both effects disappear when other attention-grabbing events, such as terrorist attacks or mass shootings, occur simultaneously with disasters. Analysis of climate change coverage across U.S. media suggests that media attention devoted to climate change concerns drives the documented shifts in investor behavior towards green investments. Furthermore, analysis of flows in brown ETFs (e.g., the oil and gas sector) reveals analogous disinvestments in the wake of disasters, but notably, only in the absence of concurrent distracting events.
Keywords: G14; G41; 330; Investor attention; green investing; natural disasters; ETFs; non-fundamental demand; green sentiment; ESG; media attention; Paris Agreement